2004
DOI: 10.1038/sj.eye.6700705
|View full text |Cite
|
Sign up to set email alerts
|

Laser vs ultrasound biometry—a study of intra- and interobserver variability

Abstract: Background Accurate biometry is of vital importance in achieving predictable postoperative refraction following cataract surgery. Aim To evaluate the accuracy and consistency in biometry, achieved by the new generation laser biometric system in comparison with the ultrasound biometric system. Methods The study was randomized and prospective. Biometry was performed in 68 eyes of 39 patients by three groups of biometrists (expert, intermediate user, novice). Expert and intermediate users are compared as group A,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 6 publications
0
27
0
1
Order By: Relevance
“…These include ultrasound A scan and B scan, slit scanning, Scheimpflug photography, and laser interferometry. [22][23][24][25][26][27][28][29][30][31] This study shows that OCT also is able to make this measurement very precisely. The interimage and interrater SD were 0, which means that the variation is less than our pixel depth (8.8 μm in aqueous).…”
Section: Discussionmentioning
confidence: 74%
“…These include ultrasound A scan and B scan, slit scanning, Scheimpflug photography, and laser interferometry. [22][23][24][25][26][27][28][29][30][31] This study shows that OCT also is able to make this measurement very precisely. The interimage and interrater SD were 0, which means that the variation is less than our pixel depth (8.8 μm in aqueous).…”
Section: Discussionmentioning
confidence: 74%
“…Kielhorn et al 31 showed that both experienced and inexperienced operators of the IOLMaster returned essentially similar measurements for IOL power. In constrast, Goel et al 32 reported that AL measurement variation between expert and non-expert operators for ultrasound biometry was 10 times higher compared with IOLMaster. In overcrowded ophthalmology clinics worldwide, we see clear advantages in adopting optical low-coherence reflectometry (OLCR) or partial coherence interferometry (PCI) devices in consultation sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Other examples exist in the field of eye [5] and head [6] biometry for health applications. Worth mentioning in the case of eye biometry is the laser system, which provides higher accuracy and consistency than the ultrasound system.…”
Section: Sound Signalsmentioning
confidence: 99%